An Update on Highly Pathogenic Avian Influenza A(H5N1) Virus, Clade 2.3.4.4b - Webby, Richard J; Uyeki, Timothy M (The Journal of infectious diseases, 2024)
Abstract Since the resurgence of highly pathogenic avian influenza (HPAI) A(H5N1) virus, clade 2.3.4.4b, during 2021, these viruses have spread widely among birds worldwide, causing poultry outbreaks and infections of a wide range of terrestrial and marine mammal species. During 2024, HPAI A(H5N1) virus, clade 2.3.4.4b, was detected in dairy cattle for the first time and caused an ongoing multistate outbreak, with high levels of virus documented in raw cow milk. Human infections with clade 2.3.4.4b viruses from exposures to infected poultry or dairy cattle have resulted in a wide spectrum of illness severity, from conjunctivitis or mild respiratory illness to severe and fatal pneumonia in different countries. Vigilance, and stronger global virologic surveillance among birds, poultry, terrestrial and marine mammals, and humans, with virus characterization and rapid data sharing, is needed to inform the threat of clade 2.3.4.4b viruses, as they continue to evolve, to public health.